(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Independence in children is very important. Characteristic of independence is children can complete their own tasks. Based on the current preliminary study, the problems that are often found are there are still children who can not be independent. One of the factors that allegedly influenced independence is parenting style. Parenting consists of 3 types of authoritarian parenting, permissive, and democratic. Objectives: To know the relationship of parenting style with the independence of preschoolers Kindergarten State Rembang. Method: This research is a kind of research of analytic survey, with cross sectional approach. The population of this research are TK Negeri Rembang students amounted to 110, and sampling method with simple random sampling method is 87 respondents. The research instrument used 2 questionnaires namely parenting style questionnaire and preschoolers self-reliance. Analysis using chi square. Results: The most widely adopted parenting style was the democratic parenting style of 54 respondents (72.0%), and the least authoritarian parenting 2 respondents (2.7%). Independence of children 64.0% children independent and not independent 27.0%. Results of analysis with chi square known X2 count <X2 table = 3,986 <5,591 and p value 0,136. Conclusion: There is no relationship between parenting style with the independence of preschool children Kindergarten State Rembang. Keywords: parenting style, Independence